Spirituality as "good Christian citizenship" in the Pastoral Epistles? - Lloyd K. Pietersen (Acta Theologica)
Dibelius, in his commentary on the Pastoral Epistles, suggested that they represented a way-of-being in the world resulting from the delay of the parousia. As such they advocate a form of spirituality which can best be described as “good Christian citizenship”. This paper, drawing on both Taylor’s understanding of the “social imaginary” and Waaijman’s understanding of spirituality, examines Dibelius’ contention by revisiting the concept of eusebeia (godliness/piety), which is prevalent in the Pastorals, in the light of the lived experience of pagans, Jews and Christians in first-century Ephesus.